Pengabidan Masyarakat Melalui Kerja Bakti di Desa Tepian Baru Kec. Bengalon - Fadli Hamzah; Muzzadi Taqwa; Ispah Sari; Ahmad Agung Perdana; Zuhal Bahry (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
The lack of community participation in community service activities can be a serious problem in efforts to build a more caring, helpful, and responsive community to shared needs. The aim is to increase community participation, generate community togetherness by being directly involved in community service, and create a clean, healthy, and comfortable environment. This service activity was carried out in the neighborhood of Tepian Baru Village, Bengalon District, East Kutai Regency. The method used in this service is the Participatory Action Research (PAR) method. The results of the dedication show that with community service participation and togetherness, the community is getting better, and the environment is clean, healthy, and comfortable. This dedication also produced works in the form of signboards and PKK program boards in the village of Tepian Baru, Bengalon District, East Kutai Regency. The hope is that community participation and togetherness will continue to be maintained for the sustainability of a clean, healthy, and comfortable environment.